10 km performance prediction by metabolic and mechanical variables: influence of performance level and post-submaximal running jump potentiation. Issue 10 (19th May 2021) - Del Rosso, Sebastián; Pinho Souza, Danilo; Muñoz, Fabián; Behm, David G.; Foster, Carl; Boullosa, Daniel
ABSTRACT: We aimed to develop models to explain performance and pacing during a 10-km running trial. Well-trained runners (n = 27, VO2max = 62.3 ± 4.5 mL·kg −1 ·min −1 ) divided into High (HPG, T10km = 33.9 ± 1.2 min, n = 9) and Low (LPG, T10km = 37.9 ± 1.2 min, n = 18) performers completed, in different days, the half squat and loaded squat jump (LSJ) exercises (1 st day), an incremental test and a submaximal running bout to induce jump potentiation (2 nd day), and a 10-km time trial (3 rd day). Pacing was significantly different between performance groups (p < 0.05). The inclusion of mechanical and metabolic variables increased the explained variance in performance (LPG, r 2 adj = 0.87, p < 0.001; HPG, r 2 adj = 0.99 p < 0.01). Analysis between potentiation and non-potentiation groups revealed significant differences for the speed in the last 400 m (p = 0.02), and in the final RPE (p = 0.03). Performance and pacing can be explained by combining metabolic and mechanical variables and should be controlled by performance level. The relationship between jump potentiation and speed during the last 400 m may suggest that post-activation performance enhancement could be involved in pacing regulation.